A critical assessment of the relationship between the AfCFTA and World Trade Organisation dispute settlement mechanisms, in light of the Conflict of Jurisdiction - Nhemachena, Tichakunda Charles (Rhodes University, Faculty of Law, Law)
This thesis interrogates the relationship between the Dispute Settlement Understanding and Africa Continental Free Trade Area dispute settlement mechanism, in light of the conflict of jurisdiction. The conflict of jurisdiction is an adverse effect of the fragmentation of international law. The uncoordinated proliferation of international treaties has increased occurrences of overlapping memberships and overlapping subject matter regulation amongst treaties. Whenever the overlaps mentioned above exist, and a dispute arises concerning matters of overlap, that dispute can be heard in more than one tribunal, giving rise to a conflict of jurisdiction. Jurisdictional conflicts are a problem because they breed uncertainty in the adjudication of disputes; they increase the risk of forum shopping, conflict of rulings, protracted litigation, and waste resources. There is a significant risk for jurisdictional conflicts between the World Trade Organisation and Africa Continental Free Trade Area agreements, because of membership and subject matter overlaps. To mitigate the problems caused by jurisdictional conflicts, the Africa Continental Free Trade Area agreement has incorporated a fork-in-the-road clause. Fork-in-the-road provisions allow parties to choose their preferred forum, and once the forum is chosen, the parties are prohibited from bringing the same dispute to another tribunal. Unfortunately, fork-in-the-road clauses are insufficient in resolving jurisdictional conflicts because they do not bind the Dispute Settlement Understanding. It is only bound to enforce World Trade Organisation obligations and not non-World Trade Organisation obligations. The extent to which non-World Trade Organisation norms apply in the Dispute Settlement Understanding is unsettled, making it difficult to conclude whether a fork-in-the-road provision will be effective an effective solution to potential jurisdictional conflicts. In this thesis, the researcher investigates the prospects of the World Trade Organisation applying the AfCFTA fork-in-the-road clause, directly, as a potential solution to the conflict of jurisdiction. In addition, the researcher will also investigate an alternative means of applying the AfCFTA fork-in-the-road provision, indirectly, using the World Trade Organisation procedural good faith provisions. In conclusion, the researcher provides recommendations on how the World Trade Organisation and the AfCFTA agreement can facilitate the application of fork-in-the-road clauses in the Dispute Settlement Understanding to resolve the conflict of jurisdiction.
Keywords: African Continental Free Trade Area; World Trade Organization; Dispute resolution (Law); Conflict of judicial decisions; Good faith (Law)